Managing Mexican Petunia (Ruellia simplex C. Wright) in the Home Landscape - Carrie A. Reinhardt Adams; Christine Wiese; L. C. Lee; Sandra B. Wilson; A. M. Smith; Rosanna Freyre (EDIS, 2014)
Environmental tolerance, abundant seed production, and an ability to easily grow from plant stem sections have allowed Mexican petunia to spread into natural areas that border urban areas. The Florida Exotic Pest Plant Council lists Mexican petunia (wild-type and non-sterile cultivars) as a Category 1 invasive species, meaning that it is “altering native plant communities by displacing native species, changing community structures or ecological functions, or hybridizing with natives.” These potential changes to community structure and ecological function are of particular concern in Florida wetlands, where changes to plant communities have the potential to impact not just plant-animal interactions, but also overall hydrology on a whole watershed level. This 6-page fact sheet was written by C. A. Reinhardt Adams, C. Wiese, L.C. Lee, S.B. Wilson, A. M. Smith, and R. Freyre, and published by the UF Department of Environmental Horticulture, April 2014.